Le politiche di genere tra «ridistribuzione» e «riconoscimento». Un percorso di lettura - Bonichi, Franca (SocietàMutamentoPolitica, 2021)
The essay is based on the international strike of March 8th 2017 and the gradual establishment of the Feminism for the 99% movement. According to theorists and activists, a class feminism able to articulate needs and political positions that speak to the complexity of experiences of ordinary women, so far neglected by the liberal dominant elite feminism. Against these events, notions like “redistribution” and “identity recognition” by Nancy Fraser, have been decisive in order to conceptualize a change which has occurred in these last decades within western politics. A transformation which has brought together the more impactful movements on the social protest level, unlike in the past, beyond a class interest perspective, as ‘groups’ or communities of value, aimed to reclaim their own identity and acquire “recognition”. A significant shift of perspective in gender politics, but also paradigmatic of the contemporary political experience in the progressive field.